Morphological changes in the pigeon’s digestive organs with salmonellosis infection - Kolomak, I. (Scientific Progress & Innovations, 2022)
Pigeons are considered the most numerous representative of the city’s avifauna, which can transmit pathogens of infectious diseases, in particular, the most common Salmonella spp. The study of pathomorphological changes in the digestive system of pigeons will allow us to analyze the changes occurring in the tissues and ensure the formation of a comprehensive approach to the prevention and treatment of salmonellosis infection. The study aimed to investigate the pathoanatomical and histological changes of the digestive organs in pigeons with salmonellosis infection. Pathomorphological studies were conducted based on the Department of Normal and Pathological Anatomy and Physiology of Animals, Poltava State Agrarian University. Bacteriological studies were carried out at the Regional State Laboratory of the State Provisional Service in the Poltava region. A general inspection of pigeon corpses revealed the absence of cadaveric suffocation; the bird was sufficiently fed and had developed muscles. The thoracoabdominal cavity contains serous fluid, the heart contained signs of right ventricular hypertrophy. In all cases (n=25), inflammation of the gastrointestinal tract was noted. When examining the small intestine, we found that the mucous membrane was red and swollen, the chyme was yellow, and mesenteric arteries had signs of venous stasis. The large intestine was thickened and had a gray-red color of the mucous membrane; the contents were liquid with impurities of mucus, green-brown in color. Histological examination of the digestive organs revealed desquamation of the epithelium in the lumen of the large intestine. The stroma of the villi had signs of swelling, the volume of epitheliocytes of the villi increased, and the cytoplasm was clear. Infiltration of intestinal epithelium by basophils is a characteristic feature. Hyperplasia of lymph nodes occurs in the wall of the small intestine, and deformation of the crypts’ apical part occurs in the large intestine. When examining the liver, the presence of hepatocytes’ dystrophic process and necrosis was established, in which hepatocytes form conglomerates of shapeless masses.